A Novel Solution for the Coupled Faults Isolation in Gear Pairs Using the Conception of Frequency Tracking - Li, Zhixiong (Elektronika ir Elektrotechnika, 2014)
In engineering practice, there is always evidence for the existence of multiply faults in the gear meshing pairs. Different failures often occur simultaneously and thus increase the complexity of fault diagnosis. A literature review indicates that very limited work has been done to address the coupled faults isolation for gear pairs. To solve this issue, this work presents a novel approach to detect coupled faults of gear pairs using a conception of Frequency Tracking. The independent component analysis with reference (ICA-R) has been employed as the fault frequency tracking tool to extract critical frequency sources from multi-channel sensors. The frequency tracking scheme uses the prior knowledge of the gear rotational frequencies to construct suitable reference signals to incorporate into the ICA-R. Then the intrinsic frequency sources excited by every failure can be separated one by one. Hence, the coupled faults are simplified into single fault isolation problem. The experimental tests were carried out to evaluate the performance of the proposed approach. The test results show satisfactory isolation of coupled gear faults. DOI: http://dx.doi.org/10.5755/j01.eee.20.3.6680